Acute Necrotizing Dermohypodermatitis Due to an Unusual Germ: Providencia Stuartii - Adama A. Dicko; Ilias Sow; Koreissi Tall; Yannick M. Nkesu; Binta Guindo; Gassama Mamadou; Yamoussa Karabinta (Dermatology, 2022)
This 33-year-old lady was hospitalised for systemic lupus and received corticosteroid therapy; upper limb edoema developed as a result. The interview revealed a theory of trauma related to a fall in the bathroom. During the examination, it was discovered that the patient’s overall health was quite poor and that her left upper limb was edematous, unpleasant to the touch, and covered in an erythematous plaque with blisters and a necrosis area. After 72-hours, ciprofloxacin, gentamycin, and amoxicillin antibiotic treatment had no noticeable effects. A bacteriological examination of the ulcer indicated the presence of Providencia stuartii, which is susceptible to cefotaxime but resistant to ciprofloxacin and amoxicillin. The biological evaluation revealed hyperleukocytosis (12,800 white blood cells/L), thrombocytopenia (103,000/L), and anaemia (9.1 g/dL). Following the administration of cefotaxime together with surgical debridement, apyrexia set in within 24-hours, and full recovery occurred three-weeks later. The search for atypical germs and the performance of an antibiogram must be mandated in front of an acute necrotizing dermohypodermatitis (AND) due to the odd location, the circumstances of the occurrence, and the clinical component.